Contrived Citizenship in Olympic Competition: Politicisation of the Olympic Games – to Divide Instead of to Unite when Para-diplomacy is Abused - Jones, David Arthur (Rethinking Asia in World Politics, 2023)
An Olympian Spirit is an ideal goal envisioned to bring outstanding athletes in many sports together in objective competition. Historical rules have been strict, some nations have skirted accepted regulations. Then more recently, multiple standards have been relaxed to the point where they seem to be non-existent or mandatory more on some than on others: both nations and athletes. This is para-diplomacy gone wild in the wrong direction. Examples are bountiful: changing of citizenship vicariously, representing countries without citizenship, testing positive for contraband substances then being allowed into competition, denial of a place in competition because the brand on a snowboard is not that of an Olympic “sponsor,” and the list goes on. Olympic training is gruelling. To allow an unqualified athlete to compete deprives a qualified athlete of an opportunity that can be life-changing. Same for fictional disqualification, medal stripping or reduction on pretext technicalities, raiding by some countries of athletes born and trained in other countries. Standards must be uniform, applicable to all competitors, enforced punctiliously by the International Olympic Committee (IOC). Alternatively, right-thinking countries will consider withdrawing from the Olympics. Is the Olympic goal only to make money, to generate media contracts, to pander to sponsors? What sanctions are appropriate? If an athlete wins a medal under a “false flag,” should that award be transferred to her/his real country? When an athlete violates a material rule, should the team of athletes representing that athlete’s country be sanctioned? If fairness is to dominate, what is fair?